Lessons from humanity: the importance of supporting families with children hospitalized for cancer - Ávila Roura, Ken Eduardo (Consorcio de Universidades Mexicanas A.C., 2018)
The current manuscript provides evidence of the importance of social networks in families with hospitalized children. It emphasizes the role of networks and their impact on family support. Additionally, it provides an example of the human capacity to be sensitive, generous and proactive for others. The sample included four families, two of which experienced the loss of their child and the other two had their children in treatment for at least a year. The study used qualitative methods with a phenomenological approach. A social poetry perspective as well as researchers as external witnesses of the stories process were used to gather family discourses.